Malaysia’s sustainable gift- a comprehensive analysis of palm oil industry - Chan, Yan Xin; Chee, Kien Ning; Lim, Poh Yee; Tan, Han Wu; Teo, Jia Min (2020)
Starting from 1960, CPO had become the main contributors to Malaysia’s Gross Domestic Product (GDP), job opportunities and export revenue until today. However, the price of CPO was fluctuated over the past decade that has brought significant negative effect to Malaysia’s economic performance. In order to achieve Sustainable Development Goals of Malaysia, sustainability of CPO industry should take into consideration. This paper investigates the key elements that affect the CPO price through three main perspectives, which are economy, financial and environment. The independent variables include CPO production, biodiesel production, crude oil price, export of CPO, exchange rate, stock price and climate change. This research examines the determinants of CPO price and identifies the combination effects of all the independent variables towards CPO price. Besides, climate change has additionally taken as interaction term in this study to examine its indirect effect towards CPO price to achieve sustainability of palm oil industry. The method utilized in this research is ARDL to examine the relationship between variables by adopting time series analysis from January 2007 to May 2018. As the result showed, crude oil price is insignificant towards CPO price under all the models due to the error term of crude oil price is not normally distributed which may lead to bias and unreliable result. Also, stock price is insignificant in all the models except for the full model with climate change as interaction. This is driven by stock price is slightly instable in the CUSUM test and tend to create a misleading conclusion and inaccurate forecast. In overall, policies will be provided at the end of the research to achieve the sustainability of palm oil industry by coping with the current issues and creating a long-lasting demand. Besides, recommendation also provided in this study for the benefits of future researchers.